Decentralized static output tracking control of interconnected and disturbed Takagi - Sugeno systems - Jabri, Dalel; Guelton, Kevin; Belkhiat, Djamel E.C.; Manamanni, Noureddine (Zielona Góra: Uniwersytet Zielonogórski)
This article describes a new procedure for the design of decentralized output-feedback tracking controllers for a class of interconnected Takagi - Sugeno (TS) fuzzy systems with external bounded disturbances and measurement noise. The main idea consists in transforming the decentralized tracking control problem, by using the descriptor redundancy formulation, to a robust decentralized stabilization one. The non-parallel distributed compensation (non-PDC) controllers proposed here are synthesized to satisfy robust H[infinity sign] tracking performance with disturbance attenuation.
Keywords: interconnected Takagi - Sugeno systems; decentralized static outputs tracking controllers; LMIs